Robert Smithson : second edition - Sullivan, Derek ([Toronto] : D. Sullivan, 2008)
A book left incomplete and open for continual revisions and additions. This incarnation finds it as a spare book in the initial stages with curious images of unlikely connections and coincidences between artist Robert Smithson and The Cure singer Robert Smith. From a group of books published by Sullivan, for his White Column's Bulletin Board project, using print on demand technology. The technology allows for the content of the titles to be under continual revision, creating an unlimited edition publication that is in perpetual development. -- www.artmetropole.com.
boek